Utilization of bauxite residue as fine aggregate for the development of structural concrete: An approach towards sustainable construction materials - Gali Kusumanjali; S. Tejas; Amit Chatterjee; Dinakar Pasla (Case Studies in Construction Materials)
Contemporary society has witnessed a significant surge in construction activities to cater to the expanding needs of the populace. The scarcity of natural resources has resulted in a predicament for the construction industry, as it encounters difficulties in obtaining high-grade fine aggregates. The present study investigates the feasibility of using bauxite residue (BR) as a partial replacement of natural sand for fine aggregates, to develop structural concrete. The first phase of the present study aims to find the optimum replacement content of BR as a partial replacement for natural sand as fine aggregates. In the second phase, a wide spectrum of concrete consisting of 20 % optimum BR content as fine aggregates (BRC20 concrete) with a w/c ratio ranging from 0.3 to 0.8 was developed, and their mechanical and long-term performance was investigated. It was observed that BRC20 concretes exhibited a strength 1.2 times higher than the control concrete mix due to the development of a dense microstructure and increased particle packing. Substitution of BR as fine aggregates in concrete is a viable option for structural concrete as all the test results fall within the prescribed limits outlined by the various codes of practice. These BRC20 concretes find their application in mainstream construction activities such as the construction of structural members for residential buildings. Applications extend to self-compacting concrete, where red mud acts as a viscosity-modifying agent, and in the production of concrete blocks and pavers for non-structural uses. These applications not only address environmental concerns associated with red mud disposal but also promote the development of innovative and eco-friendly construction materials.